(untitled) (IITM Journal of Business Studies, 2024)
Empirical research work has been done to comprehend the relationship between foreign exchange rates and the stock market. This review article provides a proper framework for the published work in this research area. The published research work is collected from the Scopus database, and bibliometric analysis is done using Bib Excel and VOS viewer. Apart from getting bibliometric results of the collected data, the findings of most cited papers are also piled up. The mixed findings of the published articles confirm the existence of a significant relationship between the stock market and foreign exchange rate. Still, the robustness of connection is highly dependent on the economic particulars of any country. It is also analyzed that the relationship appears more potent in the crisis period. This systematic analysis facilitates researchers to focus on this research area to get a more specific conclusion in this research area.